Content Marketing, Discount, Shopping Lifestyle Terhadap Impulse Buying Produk Fashion di Shopee - Salma, Selyasofa Zulfarikhatus; Huda, Nurul (Jurnal E-Bis, 2025)
The Shopee mobile platform is new to Southeast Asia and offers a variety of products and the most commonly found are fashion products, Because of the many purchases made by consumers on online shopping websites, especially shopee users, consumers often do not realize that the products they buy are not the products they need. This phenomenon is often referred to as impulse buying. This study aims to analyze the effect of content marketing, discounts, and shopping lifestyle on impulse buying. The method used in this research is Purposive Sampling, with a total sample size of 96 samples. An online survey using a questionnaire (Google Form) was used as an instrument to collect data. The data analysis process was carried out using Structural Equation Modeling- Partial Least Square (SEM-PLS). The results obtained from the study can be concluded that content marketing and discounts have a significant effect on impulse buying, but there is one variable that does not have a significant effect, namely shopping lifestyle.